Tanggung Jawab Orang Tua Atas Perbuatan Melawan Hukum Yang Dilakukan Oleh Anak Di Bawah Umur Menurut Hukum Perdata - Nunuhitu, Tiara Gracela; Jacob, Yossie M Y; Dju Bire, Chatryen M (Law Faculty, Nusa Cendana University, 2025)
Based on Article 1367 of the Civil Code, parents are responsible for the actions of minors, unless they can prove that they have provided sufficient supervision to prevent such actions. This principle is based on the concept of vicarious liability, which shifts legal responsibility from children to parents or those responsible for the care and development of children. The problems discussed in this journal are: (1) How is the responsibility of parents for unlawful acts committed by minors according to civil law? and (2) How are the settlement efforts applied when minors commit unlawful acts? The research used is normative legal research with a statutory approach and a conceptual approach. The results of the study show that in cases of unlawful acts committed by minors, parents can be held civilly liable in the form of compensation to the victim. However, in practice, dispute resolution mechanisms are more often carried out through non-litigation approaches such as deliberation and mediation in order to avoid negative impacts on the child's psychological development. The study also found that although Indonesian civil law regulates parental responsibility, there are still challenges in proving adequate supervision and in ensuring a balance between protecting the rights of victims and the best interests of the child.